Implementation of Good Governance in Indonesia in an Effort to Minimize Corruption Crime - Yusrina Handayani (Universitas Muhammadiyah Palu, 2025)
Corruption is one of the biggest challenges in governance in Indonesia, which adversely affects national development and public trust in the government. This research aims to analyze how the implementation of good governance principles, such as transparency, accountability, participation, and law enforcement, can minimize corruption. Using a descriptive-analytical qualitative approach, data were obtained through documentation studies, in-depth interviews, and participatory observations in various government agencies at the central and local levels. The results show that the main obstacles in the implementation of good governance include the lack of public access to public information, weak internal supervision, low public participation in the decision-making process, and injustice in law enforcement against perpetrators of corruption. Strategies such as data digitization through e-governance, strengthening internal and external audits, increasing participation through public consultation forums, and reforming the legal system have proven to have a positive impact in creating cleaner and more accountable governance.This study concludes that consistent and integrated application of good governance principles can reduce the potential for corruption while increasing public trust in government. The success of this strategy requires political commitment, increased institutional capacity and broad community involvement. This study makes an important contribution to developing public policy and governance practices in Indonesia, while offering an implementation model that is adaptive to the local context. With a holistic approach, this research is expected to serve as a reference for future corruption eradication efforts.